2014
DOI: 10.3390/molecules190811860
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam-Induced Immobilization of Laccase on Porous Supports for Waste Water Treatment Applications

Abstract: Abstract:The versatile oxidase enzyme laccase was immobilized on porous supports such as polymer membranes and cryogels with a view of using such biocatalysts in bioreactors aiming at the degradation of environmental pollutants in wastewater. Besides a large surface area for supporting the biocatalyst, the aforementioned porous systems also offer the possibility for simultaneous filtration applications in wastewater treatment. Herein a "green" water-based, initiator-free, and straightforward route to highly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…This way, links between the polymer matrix and the enzyme can be formed that are assumed to be side-unspecific. Previous work demonstrated the formation of covalent chemical bonds between the membrane polymer and the immobilized molecules by XPS analysis, which was supported by extensive extraction experiments [22][23][24]26,47]. It is worth emphasizing that the use of an aqueous system is a crucial requirement since different results were obtained in the dry state as also reported in the literature [48].…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…This way, links between the polymer matrix and the enzyme can be formed that are assumed to be side-unspecific. Previous work demonstrated the formation of covalent chemical bonds between the membrane polymer and the immobilized molecules by XPS analysis, which was supported by extensive extraction experiments [22][23][24]26,47]. It is worth emphasizing that the use of an aqueous system is a crucial requirement since different results were obtained in the dry state as also reported in the literature [48].…”
Section: Resultssupporting
confidence: 53%
“…The EB treatment results in the generation of a mixture of ions, excited molecules and free radicals as described for the radiolysis of water [45] ensuring the activation of both the dissolved trypsin [25,26,46] as well as of the membranes [22][23][24][27][28][29]47]. The formed radicals/activated species can undergo various reactions, such as cross-linking or recombination reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow rate was adjusted to 0.5 ml/min. A wavelength range from 220 to 400 nm was recorded (detection wavelength: 278 nm) [ 39 ]. External standards of commercial 2,5-DMBQ and self-produced 2,5-DMHQ (see above) were used for calibration.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that mediator immobilization is an effective way to achieve this goal, and the successful immobilization of several artificial on various materials has been reported. For example, a Lac redox mediator (ABTS) was immobilized on a macroporous cryogel by electron irradiation to assist the Laccatalyzed degradation of bisphenol A [32]. In addition, ABTS had been successfully attached to silica nanoparticles and a mesoporous metal-organic framework, and the immobilized ABTS played a similar role to free ABTS in mediating Lac-catalyzed dye decolorization [14,15].…”
Section: Reusability Of Sa@mnpsmentioning
confidence: 99%